Eksplorasi Lumut (Bryophyta) di Kawasan Air Terjun Bukit Gatan Provinsi Sumatera Selatan - Utami, Febri Yulia; Harmoko, Harmoko; Fitriani, Linna (Al-Hayat: Journal of Biology and Applied Biology, 2020)
This study aims to determine the type of moss in the Bukit Gatan Waterfall Region of Ulu Terawas STL Musi Rawas Regency, as well as Abiotic Factors in the Bukit Gatan Waterfall Area in the District of Ulu Terawas STL Musi Rawas District. This research is descriptive Descriptive: direct observation in the location of the Bukit Gatan Waterfall Area, STL Ulu Terawas Musi Rawas Regency with a roaming method or exploring the Waterfall Area. Data were analyzed descriptively qualitatively. Types of moss found in 2 Classes namely Bryopsida and Hepaticopsida, consisting of 5 Orders namely Pottiales, Bryales, Fissidentales, Hypnales, and Jungermaniales, consisting of 5 Families namely Pottiaceae, Batramiaceae, Fissidentaceae, Hypnaceae and Plagiochilaceae, consisting of 6 Genus Hyophila, Philotiphll, Philotropll , and Plagiochila, consisting of 7 species namely Hyophila javanica, Philonotis hastata, Fissidens atroviridis, Hyophila apiculata, Ectropothecium sp., Taxiphyllum sp., and Plagiochila asplenoides. The Abioic Factor is pH Temperature which is an average of 6.6, temperatures with an average of 27 ÂºC, humidity with an average of 6.3% and at an appropriate light intensity of 285lux.